+0  
 
+1
169
1
avatar+4690 

Help.

 Jan 30, 2018

Best Answer 

 #1
avatar+7348 
+3

\(\quad\,\frac{\sqrt3-\sqrt6}{\sqrt3+\sqrt6} \\~\\ =\,\frac{\sqrt3-\sqrt6}{\sqrt3+\sqrt6} \,\cdot\,\frac{\sqrt3-\sqrt6}{\sqrt3-\sqrt6}\\~\\ =\,\frac{3\,-\,2\sqrt{18}\,+\,6}{3\,-\,6} \\~\\ =\,\frac{9-2\sqrt{18}}{-3} \\~\\ =\,\frac{9-6\sqrt{2}}{-3} \\~\\ =\,-3+2\sqrt2\)

.
 Jan 30, 2018
 #1
avatar+7348 
+3
Best Answer

\(\quad\,\frac{\sqrt3-\sqrt6}{\sqrt3+\sqrt6} \\~\\ =\,\frac{\sqrt3-\sqrt6}{\sqrt3+\sqrt6} \,\cdot\,\frac{\sqrt3-\sqrt6}{\sqrt3-\sqrt6}\\~\\ =\,\frac{3\,-\,2\sqrt{18}\,+\,6}{3\,-\,6} \\~\\ =\,\frac{9-2\sqrt{18}}{-3} \\~\\ =\,\frac{9-6\sqrt{2}}{-3} \\~\\ =\,-3+2\sqrt2\)

hectictar Jan 30, 2018

22 Online Users

avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.